2004
DOI: 10.1002/jcb.10791
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal environmental changes modulate the prolactin receptor expression in an eurythermal fish

Abstract: Eurythermal fish have evolved compensatory responses to the cyclical seasonal changes of the environment. The complex adaptive mechanisms include the transduction of the physical parameters variations into molecular signals. Studies in carp have indicated that prolactin and growth hormone expression is associated with acclimatization, suggesting that the pituitary gland is a relevant physiological node in the generation of the homeostatic rearrangement that occurs in this adaptive process. Here, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Research on the complex adaptive mechanisms underlying fish acclimatization have indicated that sensing of the changes in physical parameters (e.g. temperature, photoperiod) and the corresponding transduction into molecular signals occurs by triggering a neuroendocrine cascade which at the same time entails transcriptional modulation in the hypothalamic-pituitary axis Kausel et al, 1999;Fletcher et al, 2001;San Martin et al, 2004). Prolactin, the well-known osmoregulatory hormone in fish appears to be also an essential coordinating molecule for temperature acclimatization San Martin et al, 2004).…”
Section: Regulation Of the Expression Of Nucleolar Proteins During Acmentioning
confidence: 99%
“…Research on the complex adaptive mechanisms underlying fish acclimatization have indicated that sensing of the changes in physical parameters (e.g. temperature, photoperiod) and the corresponding transduction into molecular signals occurs by triggering a neuroendocrine cascade which at the same time entails transcriptional modulation in the hypothalamic-pituitary axis Kausel et al, 1999;Fletcher et al, 2001;San Martin et al, 2004). Prolactin, the well-known osmoregulatory hormone in fish appears to be also an essential coordinating molecule for temperature acclimatization San Martin et al, 2004).…”
Section: Regulation Of the Expression Of Nucleolar Proteins During Acmentioning
confidence: 99%
“…These data are consistent with our observations. A discrepency between PRLR-SF mRNA levels and protein levels has also been observed in carp, where the PRLR-SF is the predominant protein even though the PRLR-LF mRNA is more abundant than the PRLR-SF mRNA (San Martin et al 2004Martin et al , 2007. The discrepancy between pPRLR-SF mRNA and protein levels could be due to increased stability of the mRNA or protein relative to the pPRLR-LF.…”
Section: Discussionmentioning
confidence: 87%